Ageing, therefore marginal: Demographic trends and institutional capacity in marginal Chilean municipalities - Giovanni Vecchio (REGION, 2022)
In Global South countries, ageing is an incoming phenomenon with socio-spatial implications that are not much explored yet. Global North countries are already facing ageing trends with significant territorial consequences, such as declining populations that contribute to making certain areas marginal. However, different factors may determine the marginality of a municipality or a region in other settings. Drawing on these premises, the paper discusses whether ageing demographic trends contribute to territorial marginality also in a Global South setting. The paper focuses on the case of Chile, a country characterised by significant territorial inequalities and a population that is becoming older. In doing so, it has a twofold purpose: first, examine census data to define what areas are currently experiencing a demographic decline and if these correspond to the areas that national policies define as marginal; second, examine official documents to consider to what extent both national policies and local development plans define ageing as an element of marginality. The decline of population in Chile defines a geography of marginality that complements and expands the one defined in policy strategies, including more areas. In contrast, institutions at different levels are only partially prepared for dealing with the socio-spatial implications of an increasingly older population.
Keywords: 330; ageing; territorial marginality; institutional capacity; Chile